Does graves’ ophthalmopathy affect anterior segment parameters? - Akmaz, Berkay; Kilic, Deniz; Akay, Fahrettin; Guven, Soner; Guven, Yusuf Ziya; Pamuk, Baris Onder (Annals of Medical Research, 2021)
Aim: To evaluate whether anterior segment parameters (ASPs) differ between patients with Graves’s ophthalmopathy (GO) and healthy individuals. Materials and Methods: In a case-control study, 62 patients with GO and 45 healthy sex- and age-matched individuals were compared for ASPs obtained from Scheimpflug camera imaging (Sirius, Florence, Italy). The ASPs were anterior chamber depth (ACD), anterior chamber volume (ACV), iridocorneal angle (ICA), corneal volume, corneal curvatures (K1, K2, and Kmean), and white-to-white, apical, and thinnest corneal thickness. Results: Mean white-to-white corneal distance, corneal volume, ACD, ACV, ICA, K1, K2, and Kmean were similar between patients and controls (p = 0.815, p = 0.285, p = 0.522, p = 0.102, p = 0.275, p = 0.114, p = 0.566, p = 0.137, p = 0.405, and p = 0.447, respectively). There was a negative correlation between mean Hertel measurement and mean ACD (r = - 0.284, p = 0.003), ACV (r = - 0.283, p = 0.003), and ICA (r = - 0.295, p = 0.002). Conclusion: The ASPs were not associated with significant alterations between patients with GO and controls.